Far-field radiative thermal rectification with bulk materials - Sarkar, Sreyash; Nefzaoui, Elyes; Basset, Philippe; Bourouina, Tarik (Journal of quantitative spectroscopy & radiative transfer, 2021)
•Far field radiative thermal rectification coefficient of 136 pairs of materials are calculated and reported.•New candidate materials for far field radiative thermal rectification are proposed.•Undoped Indium Arsenide (InAs) has a thermal rectification ratio reaching 96.35% in combination with other materials. Materials widely used in several applications where radiative thermal rectification is nonnegligible are also pointed out.•Obtained results pave the way for an optimized design of thermal radiation control and management devices such as thermal diodes. In this paper, we explore the far-field radiative thermal rectification potential of common materials such as metals,ceramics and doped semi-conductors using radiative and thermo-radiative properties extracted from literature. Seventeen different materials are considered. The rectification coefficient is then calculated for 136 pairs of materials; each pair can be used for the two terminals of a radiative thermal diode. A thermal bias of 200 K is considered. The choice of materials and thermal bias value are only bound by data availability in literature. Obtained results, highlight new candidate materials for far-field radiative thermal rectification. They also highlight materials where thermal rectification is not negligible and should be considered with care in heat transfer calculations when considering systems subject to a comparable thermal bias and where these materials are used. Among the materials studied, undoped Indium Arsenide (InAs) shows great promise to be employed for thermal rectification, with a thermal rectification ratio reaching 96.35% in combination with other materials. Obtained results pave the way for an optimized design of thermal radiation control and management devices such as thermal diodes.